Social robots in advanced dementia - Valentí Soler, Meritxell; Agüera-Ortiz, Luis; Olazarán Rodríguez, Javier; Mendoza Rebolledo, Carolina; Pérez Muñoz, Almudena; Rodríguez Pérez, Irene; Osa Ruiz, Emma; Barrios Sánchez, Ana; Herrero Cano, Vanesa; Carrasco Chillón, Laura; Felipe Ruiz, Silvia; López Alvarez, Jorge; et al. (Frontiers in Aging Neuroscience, 2015)
Aims: Testing the effect of the experimental robot-based therapeutic sessions for patients with dementia in: a controlled study of parallel groups of nursing home patients comparing the effects of therapy sessions utilizing a humanoid robot (NAO), an animal-shaped robot (PARO), or a trained dog (DOG), with conventional therapy (CONTROL) on symptoms of dementia; and an experience for patients who attend a day care center, comparing symptom prevalence and severity before and after sessions utilizing NAO and PARO. Methods: In the nursing home, patients were randomly assigned by blocks, based on dementia severity, to one of the 3 therapeutic groups to compare: CONTROL, PARO and NAO (phase 1) and CONTROL, PARO and DOG (phase 2). In the day care center, all patients received therapy with NAO (phase 1) and PARO (phase 2). Therapy sessions were held 2 days/week for 3 months. Evaluation at baseline and follow-up was carried out by blind raters using: the Global Deterioration Scale (GDS), the Severe Mini Mental State Examination (sMMSE), the Mini Mental State Examination (MMSE), the Neuropsychiatric Inventory (NPI), the Apathy Scale for Institutionalized Patients with Dementia Nursing Home version (APADEM-NH), the Apathy Inventory (AI) and the Quality of Life Scale (QUALID). Statistical analysis included descriptive statistics and non parametric tests performed by a blinded investigator. Results: In the nursing home, 101 patients (phase 1) and 110 patients (phase 2) were included. There were no significant differences at baseline. The relevant changes at follow-up were: (phase 1) patients in the robot groups showed an improvement in apathy; patients in NAO group showed a decline in cognition as measured by the MMSE scores, but not the sMMSE; the robot groups showed no significant changes between them; (phase 2) QUALID scores increased in the PARO group. In the day care center, 20 patients (phase 1) and 17 patients (phase 2) were included. The main findings were: (phase 1) imp